2019
DOI: 10.18006/2019.7(2).138.147
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Description of Novel Phaius Primary Hybrid (Orchidaceae)

Abstract: Popularly known nun orchid or swamp orchid (Phaius sps.) is listed as endangered species under Schedule-I of Indian Wild Life (Protection) Act, 1972. Natural Phaius hybrids were not reported and present study is an attempt to develop a new Phaius species by using two native species viz., Phaius tankervilleae (Banks ex l'Heritier) Bl and Phaius flavus (Blume) Lindl. Result of present study suggests crossability and compatibility between these two species which helped in synthesize novel hybrid species. New Phai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…which are widely distributed across India, China, Malaysia, Indonesia, Papua New Guinea, some Pacific Islands, and Australia (Simmons et al 2018). Several species from Phaius genus are known as decorative plants which are noticeable through their color, size, shape, number of flower buds, stem length, and durable freshness (Devadas et al 2019). Based on the stock within the Sicikeh-cikeh timberland, it is known that there are at slightest 102 species from 30 genera of orchids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which are widely distributed across India, China, Malaysia, Indonesia, Papua New Guinea, some Pacific Islands, and Australia (Simmons et al 2018). Several species from Phaius genus are known as decorative plants which are noticeable through their color, size, shape, number of flower buds, stem length, and durable freshness (Devadas et al 2019). Based on the stock within the Sicikeh-cikeh timberland, it is known that there are at slightest 102 species from 30 genera of orchids.…”
Section: Introductionmentioning
confidence: 99%
“…(Hartati et al 2019a); Phaius spp. (Devadas et al, 2019;Hartati et al 2021). The objective of this study is to determine the similarity of five natural Phaius species based on qualitative morphological characters to select the prospective parents for crossing efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Self-incompatibility and cross ability calculated by the index of self-incompatibility (ISI) indicated that P. mishmensis and P. tankervilliae are self-compatible orchids. Previous studies showed that cross-pollination between P. tankervilliae (♀) and P. flavus (♂) and their reciprocal cross, as well as self-pollinated P. tankervilliae, formed capsules with successful seed development, indicating cross compatibility among Phaius species and self-compatibility within species [9]. Pod setting provides a common measure of reproductive success in orchid breeding [29].…”
Section: Discussionmentioning
confidence: 99%
“…The Phaius genus is also being used for breeding improvement to develop new hybrids by self-pollination, interspecific cross-pollination and intergeneric-cross-pollination, but there are no reports on in vitro germination of Phaius hybrid seeds. Some success has been recorded in the development of hybrids, such as Phaius longicornu × Phaius grandiflora "Masoko" hybrid, Calanthe dominii hybrid from Calanthe masuca × Calanthe fucata [8] and "Kryptonite", a native hybrid from Calanthe rozel × P. tankervilliae [9]. However, visualizing the phenotypic traits of hybrids necessitates a long cycle of development and flowering time.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Phaius consists of 30 species in tropical parts of Asia, Australia, Africa, and various islands in the Pacific Ocean and the Indies. The Phaius orchid has a high selling value because it has large flower sizes and various colors [3]. Phaius spp needs a habitat with certain characteristics to live.…”
Section: Introductionmentioning
confidence: 99%